2011
DOI: 10.3354/meps09305
|View full text |Cite
|
Sign up to set email alerts
|

Elasmobranch egg capsules associated with modern and ancient cold seeps: a nursery for marine deep-water predators

Abstract: At 2 modern deep-water cold-seep sites, the North Alex Mud Volcano (eastern Mediterranean Sea, water depth ~500 m) and the Concepción Methane Seep Area (south-east Pacific Ocean, water depth ~700 m), we found abundant catshark (Chondrichthyes: Scyliorhinidae) and skate (Chondrichthyes: Rajidae) egg capsules, respectively, associated with carbonates and tubeworms. Fossilized catshark egg capsules were found at the 35 million year old Bear River Cold-Seep Deposit (Washington State, USA) closely associated with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 33 publications
(35 reference statements)
0
50
0
2
Order By: Relevance
“…In fact, once exhumed, they serve as hard substrates to sessile marine organisms within an otherwise vast area dominated by loose sediment (Cordes, 2009;Liebetrau et al, 2010), promoting higher diversity by providing additional ecological niches ( Fig. 9; see also Treude et al, 2011). The largest bryozoan limestone slab with its upper side fouled by a variety of encrusting organisms (Fig.…”
Section: Chronological Constraints On the Genesis Of The Bonaccia Carmentioning
confidence: 96%
“…In fact, once exhumed, they serve as hard substrates to sessile marine organisms within an otherwise vast area dominated by loose sediment (Cordes, 2009;Liebetrau et al, 2010), promoting higher diversity by providing additional ecological niches ( Fig. 9; see also Treude et al, 2011). The largest bryozoan limestone slab with its upper side fouled by a variety of encrusting organisms (Fig.…”
Section: Chronological Constraints On the Genesis Of The Bonaccia Carmentioning
confidence: 96%
“…Some of the more pervasive, important regional habitats include seamounts, canyons and channels, fjords, hydrothermal vents, and methane seeps (RamirezLlodra et al, 2010;Treude et al, 2011;Fig. 1).…”
Section: A R Thurber Et Al: Ecosystem Function and Services Providmentioning
confidence: 99%
“…Chemosymbiotic mollusks are typical of Washington State methane seeps (Goedert et al, 2003;Kiel, 2006). The mollusks found at the Behemotops site are not known to be chemosymbiotic species, and vertebrate materials, other than shark teeth (Goedert and Kaler, 1996) and elasmobranch egg capsules (Treude et al, 2011), have not been reported from Washington State methane seep sites. For these reasons, the Behemotops site is considered to be different from the site reported by Nesbitt et al (2010).…”
Section: Localitymentioning
confidence: 96%